2016
DOI: 10.1103/physrevc.94.044312
|View full text |Cite
|
Sign up to set email alerts
|

Generalized-seniority pattern and thermal properties in even Sn isotopes

Abstract: Even tin isotopes of mass number A = 108 ∼ 124 are calculated with realistic interactions in the generalized-seniority approximation of the nuclear shell model. For each nucleus, we compute the lowest ten thousand states (5000 of each parity) up to around 8 MeV in excitation energy, by allowing as many as four broken pairs. The lowest fifty eigen energies of each parity are compared with the exact results of the large-scale shell-model calculation. The wavefunctions of the mid-shell nuclei show a clear pattern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…These fitting parameters should be fine-tuned to generate optimum interactions for VDPC+HFB. In addition, higher-order correlations beyond VDPC can be included, for example, by the generalized-seniority truncation of the shell model [28,[36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…These fitting parameters should be fine-tuned to generate optimum interactions for VDPC+HFB. In addition, higher-order correlations beyond VDPC can be included, for example, by the generalized-seniority truncation of the shell model [28,[36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies on the seniority coupling scheme may be found in Refs. [2,[11][12][13][14][15]. One can also derive the exact solution of the pairing Hamiltonian by diagolizing the matrix spanned by the seniority v = 0, spin I = 0 states which represent only a tiny part of the total wave function.…”
Section: The Effective Interaction and Its Optimisation Of The Monopomentioning
confidence: 99%
“…In realistic applications usually the number of t [γ1γ2...γr] α1α2...αp;β1β2...βp (13) is still too large to fit into memory, and further simplification is necessary. On the spherical single-particle basis, we switch to the 'occupation number representation' [62][63][64]…”
Section: Many-pair Density Matrixmentioning
confidence: 99%
“…The generalized seniority quantum number, emphasizing pairing, was proposed [49][50][51][52][53] in the spherical shell model and frequently used as a truncation scheme [22,[54][55][56][57][58][59][60][61]. We recently proposed an algorithm [62] that greatly reduces the computer time cost and promotes the generalized-seniority truncation to an accurate tool for semi-magic nuclei [63,64]. The concept of generalized-seniority can be straightforwardly extended to be defined on a deformed (for example Nilsson) single-particle basis.…”
Section: Introductionmentioning
confidence: 99%